(untitled) (Journal of the College of Basic Education, 2025)
The results of the current study showed that twenty-five samples were collected for the age group 15-30 years, fifteen samples for the age group 30-45 years, and ten samples for the age group 45-60 years from burn wounds of different ages from the Specialized Burns Hospital in the Medical City for both sexes.The results showed that 24 (48%) of the samples were obtained from hand burns, 15 (30%) from chest and abdominal burns, and 11 (22%) from burns in the thigh and leg area. The samples taken according to the cause of the burns were 21 (42%) due to hot water or hot liquids, followed by 17 (34%) due to the use of hot tools, and 12 (24%) due to chemicals.Fifty pathogenic bacteria were obtained from burn samples. The number of bacteria isolated from burn wounds was 29 isolates from males, while the number was 21 isolates from females. Bacteria were cultured on differential agar cultures and some biochemical tests were performed. The predominant bacteria was (Staphylococcus aureus) 28 samples (56%) and 22 samples (44%) for (Pseudomonas aeruginosa). The age groups most affected were 15-30 years old because they are the most active groups in our daily life.